2019
DOI: 10.1097/md.0000000000017432
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of high stanniocalcin 2 expression in solid cancers

Abstract: Background:Several studies have explored the prognostic value of stanniocalcin 2 (STC2) in various cancers, but obtained inconsistent results. Therefore, this meta-analysis was performed to determine the prognostic and clinicopathologic significance of STC2 in various cancers.Methods:Eligible studies were identified by searching the online databases PubMed, Embase, Web of Science, and the China National Knowledge Infrastructure up to March 2019. Hazard ratios (HRs) with 95% confidence intervals (CIs) and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…In this study, we found that STC2 is overexpressed in OSCCs in comparison with normal oral mucosa, and its expression is associated with advanced clinical stage, shortened disease-free survival and poor disease-specific survival. These results are in line with previous ones regarding many solid cancers [10] and with the findings of Yang and collaborators [14] on 298 patients with HNSCC (tumors from oral cavity, oropharynx, pharynx and larynx). Interestingly, the expression levels of STC2 were significantly related to the clinical stage of tumor but there were no large alterations in the hazard ratios and its significance on multivariate compared to univariate analysis in our survival analysis, and our findings were validated with a different antibody in an independent cohort, supporting that STC2 is a promising and independent prognostic biomarker for OSCCs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we found that STC2 is overexpressed in OSCCs in comparison with normal oral mucosa, and its expression is associated with advanced clinical stage, shortened disease-free survival and poor disease-specific survival. These results are in line with previous ones regarding many solid cancers [10] and with the findings of Yang and collaborators [14] on 298 patients with HNSCC (tumors from oral cavity, oropharynx, pharynx and larynx). Interestingly, the expression levels of STC2 were significantly related to the clinical stage of tumor but there were no large alterations in the hazard ratios and its significance on multivariate compared to univariate analysis in our survival analysis, and our findings were validated with a different antibody in an independent cohort, supporting that STC2 is a promising and independent prognostic biomarker for OSCCs.…”
Section: Discussionsupporting
confidence: 92%
“…Besides the canonical function in calcium/phosphate regulation, promoting inorganic phosphate-induced mineralization and preventing ectopic calcification, STC2 has been related to proliferation, apoptosis, invasion and epithelial-mesenchymal transition (EMT) when upregulated in tumors [7][8][9]. A recent systematic review and meta-analysis revealed that high STC2 levels are frequently associated with advanced disease stage, lymph node metastasis and vascular invasion, factors that suggest worse prognosis, and most important, the high expression of STC2 significantly predicted poor overall survival [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is upregulated in response to metabolic stresses, including hypoxia conditions (216), and forms part of the unfolded protein response (217). STC2 is also a tumor marker for several cancers as well as possibly involved in metastasis (218,219). Studies on STC2 have not been performed in reptiles, while expression patterns have been assessed in avian muscle and joint development (220).…”
Section: Discussionmentioning
confidence: 99%
“…All the included articles were cohort studies published between 2007 and 2019. These studies included patients from various regions who were diagnosed with 11 different types of cancer: ovarian cancer (OC) [8,12], osteosarcoma (OSC) [20], colorectal cancer (CRC) [21], gastric 2 Disease Markers cancer (GC) [22,23], cholangiocarcinoma (CCA) [24,25], esophageal squamous cell carcinoma (ESCC) [26,27], pancreatic cancer (PC) [28], breast cancer (BC) [29], hepatocellular carcinoma (HCC) [30], gallbladder cancer (GBC) [31], and non-small cell lung cancer (NCSLC) [32]. All 17 cohorts reported data on OS, and 10 cohorts presented data on DFS.…”
Section: Literature Search and Included Studiesmentioning
confidence: 99%
“…Cancer is one of the leading contributors to morbidity and mortality, with approximately 1,735,350 new cancer cases and 609,640 cancer-related deaths reported in the United States in 2018 [ 1 ]. Despite great advances in early detection and comprehensive treatment in recent years, most cancers still have poor prognosis [ 2 , 3 ]. Early diagnosis and treatment monitoring can improve the prognosis of patients with cancer [ 4 ].…”
Section: Introductionmentioning
confidence: 99%